IMPACT OF BRAND, COUNTRY OF ORIGIN, TRUST IN COMPANY, AND PRICE TOWARDS BUYING DECISION (CASE HAIR EXTENSION PRODUCT IN SURABAYA - J.E. Sutanto; Ryan Hartanto Winata (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The propose of the study are to find out whether the brand, country of origin, trust towards company, and the price in effect on hair extension product purchasing decisions in Surabaya This type of research is explanatory research, because this study aims to analyze the relationship between one variable with another variable or how a variable affects another variable. This study uses quantitative methods where the method of this study used a sample and using quantitative data or statistical. This population was drawn from all residences aged 15-44 years in Surabaya and the numbers there are 1.537.077 people. This study uses non-probability sample design, which means the selection of samples based on the assessment of individual elements in the selection process. From the test results of partial and simultaneous that the brand, country of origin, trust in company, and prices significantly influence the purchase decisions of products hair extensions in Surabaya.Key Words : brand, country of origin, trust in company, price, purchase decision.